2003
DOI: 10.1097/00005392-200302000-00051
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pediatric Urolithiasis in Pakistan: Experience With 1,440 Children

Abstract: The use of ESWL, percutaneous nephrolithotomy and ureterorenoscopy has resulted in treating a large number of children with a short hospital stay and early return to school. Open surgery is reserved only for complex stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 0 publications
1
33
0
5
Order By: Relevance
“…Pakistan is situated in the middle of Afro-Asian stone belt, a high region of stone incidence. 1 Stone disease is an increasing problem in the Sindh province. 2 Geographic variation in the rates of urinary stones has been observed for many years not only among countries with higher rates in industrialized nations compared with developing and Third World countries 3 Countries of the region show wide variations in prevalence and the site of stone disease.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan is situated in the middle of Afro-Asian stone belt, a high region of stone incidence. 1 Stone disease is an increasing problem in the Sindh province. 2 Geographic variation in the rates of urinary stones has been observed for many years not only among countries with higher rates in industrialized nations compared with developing and Third World countries 3 Countries of the region show wide variations in prevalence and the site of stone disease.…”
Section: Introductionmentioning
confidence: 99%
“…In total, we included 41 patients (35 boys and 6 girls), with mean age 7.4 ± 3.1 years (range: [2][3][4][5][6][7][8][9][10][11][12][13][14][15] …”
Section: Resultsmentioning
confidence: 99%
“…5 Concerns about PCNL in children include small kidneys, possible deleterious effects on renal function, and the risk of major complications, including sepsis and bleeding. 10 Changes in technique and instrumentation have changed the management of pediatric stone disease. Therefore, PCNL is increasingly being used as monotherapy or in combination with SWL to treat staghorn stones in children.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors showed that ESWL of lower ureteral stones is not as effective as in stones of the upper urinary tract due to certain difficulties in visualizing stones overlying the sacrum (11). According to Hammad et al however, the efficiency of ESWL in the ureter may increase with a higher number of shock waves delivered (12).…”
Section: Commentsmentioning
confidence: 99%